Open Air Exploding Arc Synthesis of Nano Cu and Cu2O - KASSAEE, M.Z.; GHAVAMI, M.; MOTAMEDI, E. (Asian Journal of Chemistry, 2010)
Low cost Cu and Cu2O nanoparticles are prepared through explosion of copper wires in a current range of 50-200 amperes, at 220 volts, in the open air. Nanomaterials are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Raman spectra. Nano sizes between 20-100 nm are detected by SEM. XRD results show facecentered cubic (fcc) crystals with an average particle size of 25 nm.